PERFECTION OF TECHNOLOGY AND EQUIPMENT FOR PRODUCTION OF PISTON RINGS SLUGS IN VERTICAL STACK MOLDS - A. P. Melnikov; M. A. Sadoha; V. V. Fonov; S. N. Grechanik (Литьë и металлургия)
Perfection of technology and the equipment for production of piston rings in vertical stack molds is shown.